Electroconvulsive Therapy and Corpus Callosum Aplasia: A 3-Year Followup - Palm, Ulrich; Strauss, Philipp; Born, Christoph; Pogarell, Oliver (Case Reports in Psychiatry, 2011)
Electroconvulsive Therapy (ECT) is a powerful treatment option in severe or chronic catatonic states and has been reported to be useful in oligophrenic patients. We report the followup medical history of a patient with corpus callosum aplasia (or agenesis) who was continuously treated with ECT over three years. First, he improved considerably after a series of ECT, but relapses of catatonia made a continuous, weekly ECT necessary. Due to the severity of the brain malformation, an add-on medication with benzodiazepines and second generation antipsychotics was necessary to treat catatonic symptoms. This case emphasises the benefits of long-term ECT in oligophrenic patients.